2020
DOI: 10.1504/ijbem.2020.106200
|View full text |Cite
|
Sign up to set email alerts
|

Financial leverage and corporate performance: does the duration of the debt ratio matters

Abstract: This paper examines the relationship between financial leverage and performance of listed firms in an emerging market, Ghana. Specifically, we examine the link between short-term, long-term and total debts on performance. We use data of 190 firm-year observations from 19 listed firms over a period of ten years (2005-2014). Fixed and random effects regression models are used to examine the financial leverage-corporate performance nexus. The result shows that total debt to total assets is negatively related to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In a favorable economic environment, financial leverage can play a major role in maximizing shareholder wealth. In the same vein, many studies confirm the positive impact of financial leverage on corporate business success (Taqi et al 2020), while some research has shown that it can be a deadly factor for companies (Alarussi and Alhaderi 2018;Appiah et al 2020). For this reason, since most Iranian companies are under severe financial pressure due to financial problems caused by economic sanctions, the importance of evaluating the role of financial leverage as a control variable in this study is prominent.…”
Section: Vaic = Cee + Hce + Scementioning
confidence: 75%
“…In a favorable economic environment, financial leverage can play a major role in maximizing shareholder wealth. In the same vein, many studies confirm the positive impact of financial leverage on corporate business success (Taqi et al 2020), while some research has shown that it can be a deadly factor for companies (Alarussi and Alhaderi 2018;Appiah et al 2020). For this reason, since most Iranian companies are under severe financial pressure due to financial problems caused by economic sanctions, the importance of evaluating the role of financial leverage as a control variable in this study is prominent.…”
Section: Vaic = Cee + Hce + Scementioning
confidence: 75%
“…Moreover, several empirical studies show that short-term debt has a significant and positive effect on corporate OE [ 56 , 57 , [67] , [68] , [69] , [70] , [71] ]. However, from the corporate perspective, long-term debt offers protection from credit supply shocks and from having to restructure and/or refinance in bad times, facilitating long-term investments and improving corporate OE, which also buffers corporate managers from the regular monitoring that short-term debt requires as it comes up for renewal [ 42 , 46 , 72 , 73 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As long as a firm has more debt in comparison to equity and preference capital, the company is assumed to be more levered [53,167]. Different evidence has shown financial leverage not only has a positive impact on corporate performance [167,168], but it also affects firm value negatively [169][170][171].…”
Section: Research Model and Variablesmentioning
confidence: 99%